2013
DOI: 10.1017/s1041610213000690
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of the components of the clock drawing test

Abstract: Various brain regions were associated with each component of the CDT. These results suggest that an assessment of these components is useful for the detection of localization of brain damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 34 publications
2
34
1
Order By: Relevance
“…Instead, other tests considered to tap frontal functions, i.e. clock drawing or semantic fluency, also rely on activation of more anterior regions of the frontal lobes and of posterior regions of temporal cortex [38,39], thus resulting less reliable to predict progression to PD-MCI.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, other tests considered to tap frontal functions, i.e. clock drawing or semantic fluency, also rely on activation of more anterior regions of the frontal lobes and of posterior regions of temporal cortex [38,39], thus resulting less reliable to predict progression to PD-MCI.…”
Section: Discussionmentioning
confidence: 99%
“…Using appropriate error classification criteria, error analysis in CDT might be useful to differentiate different types of dementia, since conceptual errors are quite frequent in AD [64], but in a recent longitudinal study conceptual errors and perseverations were more frequently observed in the advanced stages of all dementing diseases, whereas spatial and planning errors were more frequent in mild-tomoderate dementia [65]. Errors in setting numbers and clock hands seem to correlate with regional hypometabolism in bilateral parietal and posterior temporal areas and in the right middle frontal gyrus [58]. By the same token, it has been recently observed that different types of errors in demented patients' performance on CDT might correlate with atrophy in different brain regions, within frontal, parietal and temporal lobes [66].…”
Section: Drawing Tasks Frequently Used In Dementiamentioning
confidence: 95%
“…In a large sample of AD patients, Shon et al [120] found that drawing from memory or copying a clock face correlated with regional glucose metabolism in bilateral temporo-parietal regions, but these correlations changed as a function of dementia severity. Matsuoka et al [58] reported another representative instance of variability in neurofunctional findings depending on the neuropsychological measure in a large sample of drug-naïve AD patients, in whom overall performance on CDT, the partial score on locating numbers of the clock and the partial score on setting the hands were correlated with atrophy in distinct parietal, posterior temporal and frontal regions. A PET study using copying of simple geometrical figure as a measure of constructional abilities showed, instead, an exclusive correlation of copying performance with the left inferior parietal lobule and the left inferior frontal gyrus [121].…”
Section: Mechanisms Giving Rise To Drawing Disorders In Ad Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…PD-patients with a flawless CDT-performance did not show this association (see Figure 2). The neuroanatomical correlates of Clock Drawing Test performance were investigated in several studies, but the findings are inconsistent [4952]. This discrepancy might probably stem from the fact that the Clock Drawing Test measures also executive function, numerical and verbal memory, and visuospatial ability [34, 53].…”
Section: Discussionmentioning
confidence: 99%